IMPLEMENTASI LESSON STUDY PADA MATA KULIAH PENGANTAR LOGIKA DI STKIP MUHAMMADIYAH KOTABUMI - Venty Meilasari (Universitas Muhammadiyah Kotabumi, 2018)
Pengantar logika which focus on teacher-centered learning leads to the lack of student involvement in learning. This study aims to describe the application of learning models TAI-based lesson study and see the impact on improving student learning activities. Application of lesson study consists of three stages: planning, implementation (do), and reflection (see). Open lesson implementation is done three times. Based on the findings of the observers, the application of lesson study is able to shift the learning paradigm from teacher-centered to student-centered. This is indicated by the more dominant student activity in learning and increasing student activity every cycle.